The United Nations, International Higher Education, and Knowledge Diplomacy - Svenson, Nanette (International Higher Education, 2016)
The United Nations is not known for international higher education involvement, yet this type of programming is increasingly prevalent within the organization. From actual universities and degree programs to higher education networks, internships and curricular development, the UN engages in a range of activities related to international higher education knowledge diplomacy. This article examines which of these initiatives may hold most potential for the UN and its member states.